Interfaith Dialogue and Unity in Diversity: A Critical Discourse Analysis of Pope Francis’s Speeches (2024) in Jakarta - Tano, Andreas (Yayasan Pendidikan Gereja Masehi Advent Hari Ketujuh Makarios, 2025)
This study employed Critical Discourse Analysis (CDA), a qualitative method to examine Pope Francis’s (2024) speeches in Jakarta, integrating ​Teun van Dijk’s socio-cognitive framework​ (2006) and ​Ruth Wodak’s discourse, historical approach (2001). As the result, the findings emerge: 1) The Pope’s rhetorical strategies; such as, ​inclusive pronouns​ (e.g., “we”) and ​metaphors​ like “bridges of dialogue”, construct collective identity and align with Indonesia’s national motto